REPRESENTATION OF SAYURI AS GEISHA IN THE NOVEL MEMOIR OF GEISHA BY ARTHUR GOLDEN - Siti Lussiyandari (Universitas Airlangga, 2020)
The aims of this study is discover how this novel constructs Sayuri as a Geisha. In order to reach that results, this study figured out the functions of the narrative and connected it into seven spheres of action. Hence, in order to analysis the data, this study used qualitative method which all of the data had to be noted, identified, and then can be explained. This study used the theory of Vladimir Propp in order to figure the narrative structure out of the novel itself. Propp provided such tools to analyze the data. There are twelve functions out from thirty one found in this study: absentation, violation, trickery, mediation, departure, the first function of donor, branding, victory, unrecognized arrived, recognition, exposure, and wedding. The researcher figured out seven spheres of action” which are in the following list: The Hero, The Villain, The Donor, The Helper, and The False Hero. Sayuri here is depicted as object of sexuality for man. Almost all of men subdued over her.